Antibacterial Testing on Silver/Zinc Oxide Nanoparticles/Organoclay Reinforced Chitosan Biocomposites - Muiz, Lisna Junaeni; Juwono, Ariadne Lakshmidevi; Paputungan, Zulkarnaen; Krisnandi, Yuni Krisyuningsih (Makara Journal of Science, 2023)
Herein, bionanocomposites of chitosan (CS)/silver nanoparticle/organoclay/zinc oxide nanoparticle (CS/Ag/OC/ZnO) were prepared for antibacterial food packaging. This study examines the time variation in the AgNP synthesis method by comparing local (74˗85% deacetylated) and commercial chitosan (75%˗85% deacetylated) as a reducing and capping agent and seeks to reconstruct the optimum ratio formulations of AgNPs and ZnONPs in bionanocomposites for food packaging. The results reveal that the synthesis of AgNPs was successfully carried out using a local chitosan solution as a reducing and capping agent. The CS/Ag/OC/ZnO films exhibit structural, mechanical, and optical properties suitable for food packaging and antibacterial activity on Staphylococcus aureus and Escherichia coli. The relative inhibition zone increased with increasing numbers of AgNPs and ZnONPs. The inhibition zone values indicated that E. coli and S. aureus bacteria were sensitive to the film, namely 12.5 ± 1.5 mm, and 16 ± 0.0 mm, respectively.